A new species and new records of the leafhopper genera Dryadomorpha Kirkaldy, 1906 and Stenogiffardia Evans, 1977 (Hemiptera: Cicadellidae: Deltocephalinae) from Equatorial Africa - Gnezdilov, Vladimir M. (Zootaxa, 2024)
A new species of the leafhopper genus Dryadomorpha Kirkaldy, 1906 (tribe Drabescini), D. tricornis sp. n., is described from the Democratic Republic of Congo. New records from Cote d’Ivoire, Cameroon, and the Democratic Republic of Congo are given for Dryadomorpha pallida Kirkaldy, 1906 and Stenogiffardia graminea (Theron, 1982) (tribe Chiasmini).